The Making of a Japanese Avant-Garde in Colonial Dairen, 1924–1937 - Culver, Annika A. (History compass, 2007)
In this article, I discuss how the Manchurian port city of Dairen became a cultural center for Japanese avant-garde literary and artistic production in the twenties and thirties. I examine the transnational flow of aesthetic and literary ideas between Tokyo and Dairen, and the economic and political factors enabling Japanese and Western avant-garde movements to flourish in this peripheral outpost of the Japanese empire. Notably, Dairen was the cradle of the Japanese surrealist movement in poetry, and later, provided a venue for an active group of surrealist artists. Though distanced from Tokyo, the central cultural and political locus of a rapidly expanding Japanese empire, Dairen served as an important crossroads in northeast Asia for trade, culture, and political ideology. Born out of Russian and Japanese imperialism, the free port of Dairen and its cosmopolitan cultural environment supported the complex historical conditions prompting a multi-faceted literary and aesthetic vision for the Japanese avant-garde.